2011
DOI: 10.1063/1.3575335
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of Au-silica nanocomposite film growth

Abstract: Thermal tweezers for nano-manipulation and trapping of interacting atoms or nanoparticles on crystalline surfaces J. Chem. Phys. 137, 114701 (2012) Thermal conductance at atomically clean and disordered silicon/aluminum interfaces: A molecular dynamics simulation study J. Appl. Phys. 112, 054305 (2012) Non-contact monitoring of Ge and B diffusion in B-doped epitaxial Si1-xGex bi-layers on silicon substrates during rapid thermal annealing by multiwavelength Raman spectroscopy AIP Advances 2, 032150 (2012) Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The alternative to semianalytical models are computer simulations, for an overview see [10]. Among recent results we mention MC simulations of ions in a magnetron discharge [15], simulation of metal atoms on polymer surfaces during PVD [16], KMC simulation of cesium superlattices on a metal substrate [17] and simulation of the growth of nanocolumns [18]. While there has been substantial progress in modeling processes in complex plasmas over the last years, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative to semianalytical models are computer simulations, for an overview see [10]. Among recent results we mention MC simulations of ions in a magnetron discharge [15], simulation of metal atoms on polymer surfaces during PVD [16], KMC simulation of cesium superlattices on a metal substrate [17] and simulation of the growth of nanocolumns [18]. While there has been substantial progress in modeling processes in complex plasmas over the last years, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Compositional patterning of metallic alloys due to phase separation was studied with kinetic Monte Carlo simulations [30,37,38]. The role of phase separation was also emphasized by kinetic Monte Carlo simulations of Au-silica nanocomposite film growth [39]. Phase separation also occurs during cone formation by ion beam sputter erosion of Si and seeding with Mo or Ni, usually performed at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This temperature rise may lead to a transiently spatiotemporal enhancement of surface migration of adatoms and chemical interaction between the landing species. Khan et al 48 indicated that the species of incident energy of 1-100 eV can create a transient temperature rise of 1000 K in a radius of 0.5-2 nm for a few picoseconds. The growth of a thin lm using atom beam sputtering takes into account the following basic processes: (i) absorption and desorption of atoms on the substrate surface, (ii) diffusion of deposited atoms on the surface, and (iii) clustering of atoms leading to the nucleation and growth of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%